2007
DOI: 10.1007/s15010-007-6304-8
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid versus Vancomycin for Prosthetic Joint Infections: a Cost Analysis

Abstract: Home-infusion of vancomycin therapy appears to be the least costly treatment approach for PJIs caused by methicillin-resistant gram-positive bacteria from the perspective of a Hong Kong public health organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…success rate was > 55%. 24 Conversely, in the third study, i.v. OPAT was found to be less cost-effective than both i.v.…”
Section: Cost-effectiveness Of Outpatient Parenteral Antimicrobial Thmentioning
confidence: 89%
See 2 more Smart Citations
“…success rate was > 55%. 24 Conversely, in the third study, i.v. OPAT was found to be less cost-effective than both i.v.…”
Section: Cost-effectiveness Of Outpatient Parenteral Antimicrobial Thmentioning
confidence: 89%
“…The patient populations were varied too, including those with surgical site infections, 66 MRSA-complicated SSTIs, 136 cystic fibrosis, 53 febrile neutropenia 65 and prosthetic joint infections. 24 Of the studies identified in the review, only one presented an incremental cost-utility analysis. 65 Using a Canadian health-care provider perspective, the authors in the study found oral antimicrobial treatment at home to be cheaper and less effective than home i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is more expensive than vancomycin as a home-infusion therapy. Hence, it is preferable to preserve it for vancomycin resistant cases [28]. …”
Section: Antimicrobialsmentioning
confidence: 99%
“…Linezolid is a potentially useful drug for the treatment of patients with bone and joint infections due to MRSA. Adverse events associated with long‐term use, such as bone marrow suppression and peripheral neuropathy, are the main issue [93–106].…”
Section: Alternatives To Classically Used Drugsmentioning
confidence: 99%